HYDROXYAPATITE (HA) ATTENUATE TIO2 TOXICITY IN BIO- SYSTEM TRIGGERING E.COLI AND MOUSE BONE MARROW MONO-NUCLEAR CELLS (BMMNC’S): Life Sciences-Immuno Biology - PUSHPENDRA MANI; HEMANT KR. SHARMA; ANKITA GAUTAM; TRIPTI SINGH; SUNIL KUMAR VERMA; RAMSHA HUSSAIN (International Journal of Life Science and Pharma Research, 2022)
The purpose of this in-vivo study was aimed to first prepare and characterize Titanium dioxide (TiO2) and Hydroxyapatite (HA) nanoparticles (NPs). Further analyzed the toxicological effect of TiO2 NPs on Bacteria E. coli, and furthermore determined the effect of TiO2 NPs, HA NPs and their applicable mingling ratio to Mouse bone marrow mononuclear cells (BMMNCs). Chemical precipitation method was used for NPs synthesis, TiO2 and HA both nano particles were characterized by X-ray diffraction (XRD) technique. Surface study of both NPs were done using Scanning Electron Microscope (SEM). Bacteria E. coli toxicity was determined by NPs incubation and optical density (O.D.) measurement. The methodology for BMMNCs toxicity determination for nano particles was first separate incubation of BMMNCs with TiO2 and HA in concentration range of 0.4 - 2mg/ml and then combined incubation of BMMNCs with TiO2 and HA in ratio 1:1 with concentration 0.4mg/ml. TiO2 and HA nano particles synthesized and characterized along with SEM surface study, TiO2 NPs were toxic for E. coli growth. The BMMNCs analysis revealed the viability of BMMNCs were very less in medium containing HA or TiO2 while it were maximum in medium containing blend of HA and TiO2. TiO2 has antibacterial property also it is toxic for BMMNCs survival but HA attenuate TiO2 cellular toxicity when applied in suitable mingling ratio of HA and TiO2 NPs. Future studies are necessary to analyze the potential application of HA and TiO2 NPs blend in cancer treatment and bone regeneration which may be useful in both cancer growth prevention and restoration of bone at the interface of implant and tissue.